Human mobility amplifies compound flood risks in coastal urban areas under climate change - Zhi-Yong Long; Huan-Feng Duan (Communications Earth & Environment)
Abstract Coastal cities face increasing compound flood risks from human mobility patterns under climate change. In this study, we integrated dynamic population distribution models with numerical hydrodynamic modelling to examine mobility effects on flood risk in Hong Kong’s Kowloon area. We simulated flooding across 75 scenarios with matching rainfall and storm surge return periods (50, 100, 200 years) under current conditions and climate projections for 2060 and 2100 under intermediate and very high emission pathways. We found human mobility causes notable temporal shifts in risk distribution, with commercial areas experiencing higher daytime risk while residential areas face increased nighttime risk. Flood risk decreases with distance from coastlines, showing distinct variations between weekdays and weekends. The Night-Day Risk Ratio reveals weekday differentials ranging from 18.7% to 20.6% with minimal weekend variations, intensifying under future climate projections. These insights inform urban planning and flood management in coastal cities.